2022
DOI: 10.1167/tvst.11.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Thinning and Temperature-Dependent Viscosity Relationships of Contemporary Ocular Lubricants

Abstract: Purpose To evaluate the shear viscosity of contemporary, commercially available ocular lubricants at various shear rates and temperatures and to derive relevant mathematical viscosity models that are impactful for prescribing and developing eye drops to treat dry eye disease. Methods The shear viscosity of 12 ocular lubricants was measured using a rheometer and a temperature-controlled bath at clinically relevant temperatures at which users may experience exposure to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…For most of the lubricants tested, increasing the angular frequencies was correlated with a reduction in viscosity, indicating the formulations have shear-thinning properties. 29 , 30 This study also showed that there were significant differences in the complex viscosities of the various commercial lubricants tested, which also corresponded to differences in NIKBUT. Overall, the NIKBUT data suggest that almost all formulations performed better than the control (without any lubricants) and PBS instillation.…”
Section: Discussionmentioning
confidence: 55%
“…For most of the lubricants tested, increasing the angular frequencies was correlated with a reduction in viscosity, indicating the formulations have shear-thinning properties. 29 , 30 This study also showed that there were significant differences in the complex viscosities of the various commercial lubricants tested, which also corresponded to differences in NIKBUT. Overall, the NIKBUT data suggest that almost all formulations performed better than the control (without any lubricants) and PBS instillation.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, they also maintain low viscosity at high shear rates, which gives better ocular comfort as well as prevents friction-related inflammation issues. [ 10 , 11 ]…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…Drop frequency should be tailored to the individual DED patient (Kim et al, 2021). Considering the huge variability in ingredients, concentrations, viscosity and other characteristics among the various products available (Kapadia et al, 2022), drop frequency should also depend on the specific product used. The heterogeneity in drop frequency across studies can be attributed to the lack of studies specifically investigating this aspect of DED treatment, as exemplified by a literature review of HA treatment for DED by our group that describes this literature gap (Hynnekleiv et al), as well as the current review in which no such studies were found.…”
Section: Tailored Ded Treatmentmentioning
confidence: 99%